Culture wars : an encyclopedia of issues, viewpoints, and voices - Chapman, Roger, 1960- (Gale virtual reference library., 2010)
Although openness and inclusion are cornerstones of life in the United States, intolerance and reactionary politics are also very real. As the nation prepares to elect a new president, The Culture Wars addresses the key defining issues of contemporary American society through the lens of political and social controversy. Featuring hundreds of A-Z entries and numerous photos, the encyclopedia examines the history and relevance of the issues, events, controversies, personalities, groups, and concepts that have contributed to the political and social polarization of American society over recent decades. It details hot-button topics as well as the role of the media in defining and shaping these issues--everything from abortion, the Christian Coalition, the environmental movement, feminism, and gay rights, to illegal aliens, pornography, stem-cell research, Watergate, and zero tolerance.